Praktik Kawin Tangkap (Piti Rambang): Konflik Hukum Adat dengan Hukum Perkawinan Nasional dan Hukum Islam: The Practice of Captive Marriage (Piti Rambang): Conflict between Customary Law, National Marriage Law, and Islamic Law - Wiwin; Auliah Ambarwati; Johamran Pransisto; Irwan Surya Darmawan; Irwan (Sekolah Tinggi Agama Islam Negeri Majene, 2025)
The practice of kawin tangkap is a traditional custom in Sumba in which a man or his family unilaterally abducts a woman to be married without her prior consent. This practice has sparked controversy due to its perceived violation of women's rights, while on the other hand, it is regarded by some as a part of customary law. This study aims to analyze the legal standing of the kawin tangkap practice from the perspective of Law No. 1 of 1974 on Marriage and Islamic law. The research employs a normative legal method with a statutory approach, analytical approach, and Islamic legal approach. The findings indicate that the practice of kawin tangkap is in conflict with Article 6 paragraph (1) of the Marriage Law, which explicitly requires the consent of both prospective spouses as a condition for a valid marriage. Consequently, a marriage conducted through kawin tangkap may be annulled pursuant to Article 22 of the Marriage Law. Furthermore, kawin tangkap contradicts Islamic law as it involves ikrah (coercion) in marriage, which is prohibited by Islamic principles and Article 16 paragraph (1) of the Compilation of Islamic Law. Although kawin tangkap is rooted in customary law, its enforcement cannot be legitimized as it violates Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia (which requires customary law to align with the principles of the Republic) and the theory of receptie a contrario (which mandates that customary law must conform to Islamic law).